Activation and recruitment of brown adipose tissue by cold exposure and food ingredients in humans. Issue 4 (August 2016) - Saito, Masayuki; Yoneshiro, Takeshi; Matsushita, Mami
Abstract : Since the recent re-discovery of brown adipose tissue (BAT) in adult humans, this thermogenic tissue has attracted increasing interest. The inverse relationship between the BAT activity and body fatness suggests that BAT, because of its energy dissipating activity, is protective against body fat accumulation. Cold exposure activates and recruits BAT in association with increased energy expenditure and decreased body fatness. The stimulatory effects of cold are mediated through transient receptor potential channels (TRP), most of which are also chemesthetic receptors for various food ingredients. In fact, capsaicin and its analog capsinoids, representative agonists of TRPV1, mimic the effects of cold to decrease body fatness through the activation and recruitment of BAT. The anti-obesity effect of some other food ingredients including tea catechins may also be attributable to the activation of the TRP-BAT axis. Thus, BAT is a promising target for combating obesity and related metabolic disorders in humans.